Instrumented indentation based methods to assess fracture toughness (KIC) of self-compacting concrete: Influence of water to binder (w/b) ratio and type of concrete. (November 2022) - Bouali, A.; Grairia, S.; Nettour, D.; Chérait, Y.; Arabi, N.; Montagne, A.; Iost, A.; Chicot, D.
Highlights: Fracture toughness (KIC ) of self-compacting concrete is studied by instrumented indentation test (IIT) using a Vickers Indenter. It is demonstrated that water-to-binder (w/b) ratio has an effect on fracture toughness of Self-compacting concretes (SCC) by instrumented indentation test. It is confirmed that self-compacting concrete (SCC) presents better fracture toughness than normal vibrated (NVC) ones with similar compressive strength. Brittleness and crack length of specimens are affected by water- to-binder (water-to-cement) ratio under same indentation loads. Abstract: The main objective of this paper is to compare the fracture toughness determined by instrumented indentation tests of a variety of self-compacting concretes (SCCs) and normal vibrated concretes (NVCs). For this purpose, five mixing compositions of self-compacting concrete (SCC) with different water/binder ratios of 0.33 to 0.41 (water/cement ratio = 0.44 to 0.56) and two mixing compositions of normal vibrated concrete (NVC) were prepared. The fracture behaviors of both (SCCs) and (NVCs) with laboratory-size specimens under the instrumented indentation test (IIT) were investigated. It was found that the fracture toughness values of the self-compacting concrete increased with the decreasing w/b ratio. The largest values of the stress intensity factor (KIC ) were showed on the concretes with the lowest (w/b) ratio (w/b = 0.33, the case of SCC5). Moreover, it is confirmed that the self-compacting concretes exhibit larger fracture toughness than those of the normal vibrated concretes at the same compressive strength. The obtained results indicated that there existed a remarkable relationship between the water/binder (water/cement) ratio, fracture behavior and mechanical properties of these materials. It is shown that the instrumented indentation technique can be very useful for determination of the fracture parameters.